Genetic Diversity in Normal Cell Populations is the Earliest Stage of Oncogenesis Leading to Intra-Tumor Heterogeneity - Howk, Cory L.; Voller, Zachary; Beck, Brandon B.; Dai, Donghai (Frontiers in Oncology, 2013)
Random mutations and epigenetic alterations provide a rich substrate for microevolutionary phenomena to occur in proliferating epithelial tissues. Genetic diversity resulting from random mutations in normal cells is critically important for understanding the genetic basis of oncogenesis. However, evaluation of the cell-specific role of individual (epi-)genetic alterations in living tissues is extremely difficult from a direct experimental perspective. We have developed a theoretical model for uterine epithelial cell proliferation. Computational simulations have shown that a base-line mutation rate of two mutations per cell division is sufficient to explain sporadic endometrial cancer as a rare evolutionary consequence with an incidence similar to that reported in SEER data. Simulation of the entire oncogenic process has allowed us to analyze the features of the tumor initiating cells and their clonal expansion. Analysis of the malignant features of individual cancer cells, such as de-differentiation status, proliferation potential, and immortalization status, permits a mathematical characterization of malignancy and a comparison of intra-tumor heterogeneity between individual tumors. We found, under the conditions specified, that cancer stem cells account for approximately 7% of the total cancer cell population. Taken together, our mathematical modeling describes the genetic diversity and evolution in a normal cell population at the early stages of oncogenesis and characterizes intra-tumor heterogeneity. This model has explored the role of accumulation of a large number of genetic alterations in oncogenesis as an alternative to traditional biological approaches emphasizing the driving role of a small number of genetic mutations, and this accumulation, along with environmental factors, has a significant impact on the growth advantage of and selection pressure on individual cancer cells and the resulting tumor composition and progression.